Integrated Biosensor for Rapid and Point-of-Care Sepsis Diagnosis - Min, Jouha; Nothing, Maria Grazia; Coble, Ben; Zheng, Hui; Park, Jongmin; Im, Hyungsoon; Castro, Cesar M.; Swirski, Filip K.; Weissleder, Ralph; Lee, Hakho; Weber, Georg (ACS nano, 2018)
Sepsis is an often fatal condition that arises when the immune response to an infection causes widespread systemic organ injury. A critical unmet need in combating sepsis is the lack of accurate early biomarkers that produce actionable results in busy clinical settings. Here, we report the development of a point-of-care platform for rapid sepsis detection. Termed IBS (integrated biosensor for sepsis), our approach leverages (i) the pathophysiological role of cytokine interleukin-3 (IL-3) in early sepsis and (ii) a hybrid magneto-electrochemical sensor for IL-3 detection. The developed platform produces test results within 1 h from native blood samples and detects IL-3 at a sensitivity of <10 pg/mL; this performance is >5-times faster and >10-times more sensitive than conventional enzyme-linked immunoadsorbent assays, the current gold standard. Using clinical samples, we show that elevated plasma IL-3 levels are associated with high organ failure rate and thus greater risk of mortality, confirming the potential of IL-3 as a sepsis diagnostic biomarker. With further system development ( e. g., full automation, data security measures) and rigorous validation studies, the compact and fast IBS could be a practical clinical tool for timely diagnosis and proactive treatment of sepsis.
EVALuna2:210713